Effect of Woolen Cloth to Maintain Temperature 39°C of Crystaloid Fluid Ringer Lactate at Room Temperature 18°C - Helna Fitriana; Abdurrahman Wahid; Tina Handayani Nasution; Gia Eka Negara (Journal of Nursing Science Update (JNSU), 2021)
Fluid resuscitation with 39ᵒC is one of the main therapies for hypovolemic (hemorrhagic) shock patients to prevent complications. In this time, we already have tools to keep the fluid warm, but not all health services have these tools.  To find out the effectiveness of using woolen cloth against the temperature of Ringer Lactate 39°C crystalloid fluid at room temperature 18°C. This study used a pre-experimental method, with a static group comparison approach, with 4 Ringer Lactate liquid samples divided into 2 groups, namely groups using wool cloth and those not using woolen cloth. Data collected through observation sheets. Data analyzed using the Mann Whitney test. With this p value (0.00001) <α (0.05), it can be concluded that there is a significant difference between the use of woolen cloth and those that do not use woolen cloth. The woolen cloth is effective to slow down the decrease in temperature of the crystalloid liquid Ringer Lactate 39ᵒC at room temperature 18ᵒC. The difference in temperature changes in the Ringer Lactate crystalloid fluid is influenced by several things including humidity, ambient temperature, and additional material used.